Shifts in subsurface oxygen transport and consumption patterns in a restored coastal flood plain over five years - Emilio Grande; Ruby N. Ghosh; Charles McIntire; Michael J. Freeman; Peter Regier; Nicholas D. Ward (Limnology and Oceanography, 2026)
Groundwater dissolved oxygen (DO) variability in coastal systems remains poorly understood despite its importance for biogeochemical cycling and ecosystem modeling. This study investigates temporal variability in groundwater DO and its hydro‐climatic drivers across timescales (hourly to seasonal) in a coastal floodplain at Beaver Creek, Washington, USA, a site transitioning from a freshwater forest to brackish tidal wetland following restoration of tidal influence. Using 5 years of high‐frequency (5‐min) hydro‐meteorological and continuous groundwater DO data, we applied wavelet and information theory analyses to disentangle the role of different drivers (e.g., groundwater levels, temperature, precipitation, among others) on DO dynamics. Monitoring was initiated 5 years after the site was restored but prior to subsurface conditions reaching a new steady state. We found that DO pulses related to tidal flooding events were most frequent during earlier water years, dominated by hourly, daily and multiday variability. In later years both the frequency and magnitude of these DO pulses decreased, resulting in more prolonged subsurface anoxia. These shifts in DO patterns reflect gradually changing subsurface biogeochemical conditions as the system continues to fully transition from lowland forest to brackish wetland 10 years after restoration. This study highlights the critical role of timescale‐specific analyses in understanding wetland biogeochemistry by identifying dominant drivers of DO variability and linking them to ecosystem transitions. Our scale‐aware approach offers a framework for evaluating ecosystem responses to climate change, sea‐level rise, and restoration efforts in tidal wetlands.

Association of area deprivation index and median household income with early postoperative outcomes after spine tumor surgery - Kristen H. Park; Joshua L. Golubovsky; Jennifer Cirvello; Emily Xu; Scott D. McClintock; Anish Butala; Gabrielle W. Peters; Alvand Hassankhani; Hayley M. Knollman; James Schuster; Colbey W. Freeman; Neil R. Malhotra (Next Research, 2026)

Multi-media occurrence, bioaccumulation, and exposure assessment of PFAS across a Midwestern U.S. State - Maria S. Sepúlveda; Lisa Brown; Staci L. Capozzi; Samantha C. Cullom; Jeffrey E. Dick; Daniel J. Foti; Ronaldo H. Franjul; Nicole L. Franklin; Jennifer L. Freeman; Carolina Gonzalez-Canas; Wanyue Hui; Yuxin Jiang; et al. (Environmental Research, 2026)

Comparing phosphatised galleried stereom of Ordovician Cincinnaticrinus to modern Endoxocrinus illustrates preservation by micromolding - Benjamin F. Dattilo; Rebecca L. Freeman; David F. Wright; David L. Meyer; James R. Thomka; Samuel Sheray; Michael Harrison; Christopher D. Aucoin (Facies, 2026)
Fossil echinoderm ossicles are often occluded by syntaxial overgrowths which obscure stereom. Phosphatized ossicles from insoluble residues show fine microstructure. We investigated phosphatized stereom in Cincinnaticrinus columnals in insoluble residues from the Ordovician around Cincinnati, Ohio USA. Microstructures appeared to be stereom micromolds. We tested this hypothesis by examining residue and thin sections of undissolved sample using light microscopy, SEM and EDS, resulting in these observations: (1) calcite within phosphatized ossicles is optically aligned and parallel to stem; (2) phosphate deposited centripetally from calcite surfaces, often incompletely filling cavities, leaving a central vug; (3) while calcite is inclusion-free, phosphate contains siliciclastic inclusions from surrounding sediments. These observations suggest that calcite is original, and phosphate was deposited as micromolds. To confirm the phosphatic micromold hypothesis, we compared internodal columnals from the extant isocrinid Endoxocrinus from the Florida Straits using fracture surfaces and epoxy-impregnated thin sections. We then dissolved the thin section calcite, leaving epoxy micromolds for comparison. Schematic 3-D models summarize our reconstructions of structure of the crinoids in both original calcite and micromolds. Through-going solid cylinders are present in Cincinnaticrinus phosphate and Endoxocrinus epoxy molds. In Endoxocrinus , these are molds of stereomic galleries complete with ligaments, confirming Cincinnaticrinus phosphate is also moldic. Galleried stereom of the two crinoids differs in structural details, a divergence that is consistent with phylogenetic evidence of through-going ligaments in an early common ancestor. Preservation by phosphatic micro-molding, interpreted as preserved negative space, facilitates study of stereomic features supporting crinoid soft tissues.

Towards cost-effective and sustainable PET recycling through glycolysis: Ethylene glycol recovery using solution-processable nanocomposite membranes - Hamidreza Mahdavi; Leonie van 't Hag; Zongli Xie; Matthew R. Hill; Benny D. Freeman (Chemical Engineering Journal, 2026)

Pancreatic islet remodeling in horses with hyperinsulinemia and pituitary dysfunction - P. Teague; M. Dark; D. Verdugo; D. Freeman; D. McFarlane (Domestic Animal Endocrinology, 2026)

Genetic structure of Sydney Cockle Anadara trapezia: Implications for stock assessment and restoration of extirpated populations - Matthew D. Taylor; Matthew Freeman; Rowan C. Chick; Laura Parker; Wayne O’Connor; Sankar Subramanian (Fisheries Research, 2026)

Household environmental characteristics influence the house dust metagenome - Isabella Gamez; Farnaz Fouladi; Antonio Gonzalez; James Ward; Ziyue Wang; Laura E. Beane Freeman; Alison Motsinger-Reif; Shyamal D. Peddada; Rob Knight; Mikyeong Lee; Stephanie J. London (Environmental Research, 2026)

Low-dose tamoxifen ameliorates ovariectomy-induced metabolic and immune dysfunction - Heather E. McClurg; Amanda Ferraro; Gina Pham; Itzel Morales-Hernandez; Estefania Valencia-Rincon; Kevin D. Pham; Willard M. Freeman; Jacquelyn A. Gorman; Marisol Castillo-Castrejon (GeroScience, 2026)
The decline in estrogen following menopause is a major driver of metabolic and immune dysfunction in aging females. While hormone replacement therapy improves many of these outcomes, its clinical use remains limited due to concerns regarding estrogen-sensitive malignancies. Tissue-selective estrogen complexes (TSECs), which combine estrogens with selective estrogen receptor modulators (SERMs) such as tamoxifen (TAM), represent a promising strategy to preserve the metabolic and immunological benefits of estrogen while reducing oncogenic risk. However, the systemic effects of TAM under conditions of estrogen deficiency remain incompletely defined. In this study, we investigated the metabolic and immunomodulatory actions of low-dose TAM, alone or in combination with 17β-estradiol (E2), in adult ovariectomized (OVX) female mice. OVX resulted in increased adiposity, hepatic steatosis, glucose intolerance, insulin resistance, immunoglobulin G3 (IgG3) concentration, and systemic inflammation, along with decreased immunoglobulin G1 (IgG1) concentration. E2, TAM, and E2 + TAM each attenuated OVX-induced adipose expansion, adipocyte hypertrophy, and proinflammatory cytokine production. TAM improved insulin sensitivity but did not fully restore glucose tolerance. Transcriptomic analysis of visceral adipose tissue-resident B cells revealed that E2 and E2 + TAM modulate overlapping yet distinct immune-regulatory networks, including suppression of pro-inflammatory signaling, regulation of immune checkpoints, and genes linked to adipose homeostasis. Low-dose TAM emerges as a modulator of estrogen receptor signaling that attenuates multiple features of OVX-induced metabolic and inflammatory dysfunction, though its limited effect on glycemic control highlights the need for tissue-specific evaluation of SERM-based interventions. These findings provide mechanistic insight into endocrine–immune–metabolic interactions and inform strategies to reduce aging-related disease risk in postmenopausal women. Graphical Abstract Created in BioRender ( https://BioRender.com/7ouhlqq ), Castillo M. (2025)

Phytoplankton Biomass Dynamics in Wet (2019) and Dry (2023) Years in Lake Pontchartrain Estuary, Louisiana from Sentinel 2-MSI and PACE-OCI Observations - Shiwani Shrestha; Bingqing Liu; Jiang Li; Wei Huang; Melissa M. Baustian; Eurico J. D'Sa; Sibel Bargu; Francesca Messina; Ioannis Y. Georgiou; Abhishek Kumar; Angelina Freeman; Scott Mize (Science of The Total Environment, 2026)

Effect of water, sanitation, and hygiene on childhood growth in Ethiopia: a cluster-randomized trial - Tahvi Frank; Isabel J.B. Thompson; Solomon Aragie; Dionna M. Wittberg; Wondyifraw Tadesse; Adane Dagnew; Dagnachew Hailu; Jason S. Melo; Taye Zeru; Zerihun Tadesse; Benjamin F. Arnold; Matthew C. Freeman; et al. (International Journal of Hygiene and Environmental Health, 2026)

The amphibians of Betampona: an updated account of the remarkable diversity of Madagascar’s central-eastern Strict Nature Reserve - Costanza Piccoli; Alessio Paoletti; Franco Andreone; Karen Freeman; Georges; D. James Harris; Honoré Lava; Martim Melo; Jean Nöel; Dina L. Ramamonjisoa; Randriamialisoa; Achille P. Raselimanana; et al. (Systematics and Biodiversity, 2025)

Enhancing strategies for advanced treatment technologies to reduce microplastic pollution - Hamidreza Mahdavi; Suer Kurklu Kocaoglu; Laila Halim; Michael Batten; Abdollah Khosravanian; Leonie van ‘t Hag; Zongli Xie; Matthew R. Hill; Benny D. Freeman (Journal of Environmental Chemical Engineering, 2025)

Animal farming and the oral microbiome in the Agricultural Health Study - Vicky C. Chang; Vaishnavi Purandare; Shilan Li; Gabriella Andreotti; Xing Hua; Yunhu Wan; Casey L. Dagnall; Kristine Jones; Belynda D. Hicks; Amy Hutchinson; Yukiko Yano; Kathryn R. Dalton; et al. (Environmental Research, 2025)

Permeate fluxes from desalination of brines and produced waters: A reactive transport modeling study - Sergi Molins; Nicolas Spycher; Sarah M. Dischinger; Mostafa Nassr; Ji Yeon Lee; Jacob Johnston; Nils Tilton; Kristofer L. Gleason; Benny D. Freeman; William T. Stringfellow; Daniel J. Miller (Applied Geochemistry, 2025)

Traditional and industrial approaches to oil palm cultivation alter the biodiversity of ground-dwelling arthropods in Liberia (West Africa) - Jonathan H. Timperley; Brogan L. Pett; Bility Geninyan; Ari Saputra; Abraham Vincent; Romeo Weah; Benedictus Freeman; Marshall Guahn; Peter M. Hadfield; Morris T. Jah; Tiecanna Jones; Rudy H. Widodo; et al. (Agriculture, Ecosystems & Environment, 2025)

Methylation array signals are predictive of chronological age without bisulfite conversion - Hunter L. Porter; Victor A. Ansere; Ram Babu Undi; Walker Hoolehan; Cory B. Giles; Chase A. Brown; David Stanford; Mark M. Huycke; Willard M. Freeman; Jonathan D. Wren (GeroScience, 2025)
DNA methylation data has been used to make “epigenetic clocks” which attempt to measure chronological and biological aging. These models rely on data derived from bisulfite-based measurements, which exploit a semi-selective deamination and a genomic reference to determine methylation states. We found that non-methylation factors lead to “pseudomethylation” signals that are both confounding of epigenetic clocks and uniquely age predictive. We also failed to predict age using human genotyping arrays, but found that epigenetic clocks were overrepresented near genomic regions whose methylation state is dependent upon sequence variants. Quantifying these covariates in aging studies will be critical to building better clocks and designing appropriate studies of epigenetic aging.

Shifting, expanding, or contracting? Range movement consequences for biodiversity - Jedediah F. Brodie; Benjamin G. Freeman; Philip D. Mannion; Anna L. Hargreaves (Trends in Ecology & Evolution, 2025)

Whole transcriptome analysis of Mycoplasma bovis-host interactions under in vitro and in vivo conditions - Aga E. Gelgie; Benti D. Gelalcha; Trevor Freeman; Taylor B. Ault-Seay; Jonathan Beever; Oudessa Kerro Dego (Veterinary Microbiology, 2025)

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Elemental composition and potential toxicity of the riverine macrophyte Podostemum ceratophyllum Michx. reflects land use in eastern North America - James L. Wood; Lee H. Dietterich; Douglas R. Leasure; Sarah C. Jantzi; Thomas R. Maddox; Seth J. Wenger; Jonathon W. Skaggs; Amy D. Rosemond; Mary C. Freeman (Science of The Total Environment, 2024)

Perspective paper: Framework to assess the potential of circular food system technologies - C. Halpern; K. Kennedy Freeman; C.B. Barrett; M. van Dijk; D. Mason-D’Croz; A. Simons; B. van Veen; M. Herrero; H.H.E. Van Zanten (Global Food Security, 2024)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

Age, pair tenure and parenting, but not face identity, predict looking behaviour in a pair-bonded South American primate - Allison R. Lau; Alexander Baxter; Shuyu He; Louise Loyant; Chelsea A. Ortiz-Jimenez; Melissa D. Bauman; Karen L. Bales; Sara M. Freeman (Animal Behaviour, 2024)

Sexually selected differences in warbler plumage are related to a putative inversion on the Z chromosome - Peter O. Dunn; Nicholas D. Sly; Corey R. Freeman‐Gallant; Amberleigh E. Henschen; Christen M. Bossu; Kristen C. Ruegg; Piotr Minias; Linda A. Whittingham (Molecular Ecology, 2024)
Large structural variants in the genome, such as inversions, may play an important role in producing population structure and local adaptation to the environment through suppression of recombination. However, relatively few studies have linked inversions to phenotypic traits that are sexually selected and may play a role in reproductive isolation. Here, we found that geographic differences in the sexually selected plumage of a warbler, the common yellowthroat ( Geothlypis trichas ), are largely due to differences in the Z (sex) chromosome (males are ZZ), which contains at least one putative inversion spanning 40% (31/77 Mb) of its length. The inversions on the Z chromosome vary dramatically east and west of the Appalachian Mountains, which provides evidence of cryptic population structure within the range of the most widespread eastern subspecies ( G. t. trichas ). In an eastern (New York) and western (Wisconsin) population of this subspecies, female prefer different male ornaments; larger black facial masks are preferred in Wisconsin and larger yellow breasts are preferred in New York. The putative inversion also contains genes related to vision, which could influence mating preferences. Thus, structural variants on the Z chromosome are associated with geographic differences in male ornaments and female choice, which may provide a mechanism for maintaining different patterns of sexual selection in spite of gene flow between populations of the same subspecies.

Conversion of rainforest to both traditional and industrial oil palm systems changes the biodiversity, web-building, and prey capture of understory spiders (Liberia, West Africa) - Michael D. Pashkevich; Brogan L. Pett; Cicely A.M. Marshall; Jean-Pierre Caliman; Benedictus Freeman; Marshall M. Guahn; Peter M. Hadfield; Matthew T. Hendren; Morris T. Jah; Tiecanna Jones; Ari Saputra; Rudy H. Widodo; et al. (Agriculture, Ecosystems & Environment, 2024)

Vaporized nicotine in utero results in reduced birthweight, increased locomotion, and decreased voluntary exercise, dependent on sex and diet in offspring - Samantha L. Penman; Nicole M. Roeder; Jia Wang; Brittany J. Richardson; Ojas Pareek; Lily Freeman-Striegel; Patrick Mohr; Anas Khan; Rina D. Eiden; Saptarshi Chakraborty; Panayotis K. Thanos (Psychopharmacology, 2024)

The socioecological benefits and consequences of oil palm cultivation in its native range: The Sustainable Oil Palm in West Africa (SOPWA) Project - Michael D. Pashkevich; Cicely A.M. Marshall; Benedictus Freeman; Valentine J. Reiss-Woolever; Jean-Pierre Caliman; Julia Drewer; Becky Heath; Matthew T. Hendren; Ari Saputra; Jake Stone; Jonathan H. Timperley; William Draper; et al. (Science of The Total Environment, 2024)

Correction: Reconnaissance Survey for Potential Energy Storage and Carbon Dioxide Storage Resources of Petroleum Reservoirs in Western Europe - Emil D. Attanasi; Philip A. Freeman (Natural Resources Research, 2023)

Characterization of novel mouse models to study the role of necroptosis in aging and age-related diseases - Ramasamy Selvarani; Hoang Van Michelle Nguyen; Nidheesh Thadathil; Roman F. Wolf; Willard M. Freeman; Christopher D. Wiley; Sathyaseelan S. Deepa; Arlan Richardson (GeroScience, 2023)
To study the impact of necroptosis-induced chronic inflammation on age-related diseases and aging, two knockin mouse models ( Ripk3 -KI and Mlkl -KI) were generated that overexpress two genes involved in necroptosis ( Ripk3 or Mlkl ) when crossed to Cre transgenic mice. Crossing Ripk3 -KI or Mlkl -KI mice to albumin-Cre transgenic mice produced hepatocyte specific hRipk3 -KI or hMlkl -KI mice, which express the two transgenes only in the liver. Ripk3 and Mlkl proteins were overexpressed 10- and fourfold, respectively, in the livers of the hRipk3 -KI or hMlkl -KI mice. Treating young (2-month) hRipk3 -KI or hMlkl -KI mice with carbon tetrachloride (CCl 4 ), a chemical inducer of oxidative stress, resulted in increased necroptosis (Mlkl-oligomers) and inflammation in the liver compared to control mice receiving CCl 4 . Mlkl-oligomerization also was significantly increased in old (18-month) hRipk3 -KI and hMlkl -KI mice compared to old control (Cre negative, Ripk3 -KI and Mlkl -KI) mice. The increase in necroptosis was associated with an increase in inflammation, e.g., inflammatory cytokines (TNFα, IL-6) and macrophage markers (F4/80, CD68). Importantly, steatosis (triglycerides) and fibrosis (e.g., picrosirius red staining, hydroxyproline levels, and transcripts for TGFβ, Col1α1, and Col3α1) that increase with age were significantly higher in the livers of the old hRipk3 -KI or hMlkl -KI mice compared to old control mice. In addition, markers of cellular senescence were significantly increased in the livers of the old hRipk3 -KI and hMlkl -KI mice. Thus, the first mouse models have been developed that allow researchers to study the impact of inducing necroptosis in specific cells/tissues on chronic inflammation in aging and age-related diseases.

Seasonal drivers of dissolved oxygen across a tidal creek–marsh interface revealed by machine learning - Peter J. Regier; Nicholas D. Ward; Allison N. Myers‐Pigg; Jay Grate; Michael J. Freeman; Ruby N. Ghosh (Limnology and Oceanography, 2023)
Dissolved oxygen (DO) is a key biogeochemical control in coastal systems, and its concentration and drivers vary markedly through time and space. This makes it difficult to accurately represent coastal DO and associated biogeochemical processes in models, limiting our ability to predict how these systems will respond to global change. We obtained high‐frequency (5‐min) in situ measurements of DO collected at three locations across the interface of a tidal creek and coastal marsh in the Pacific Northwest, USA. Random Forest machine learning models quantified the importance of three categories of environmental drivers (Aquatic, Climatic, and Terrestrial) of DO variability across the creek–marsh interface. We selected two 4‐month datasets representing Summer and Winter seasonal periods to test two hypotheses on the dominant drivers of DO at the coastal interface. We found that the Terrestrial driver—characterized by long periods of anaerobic conditions and episodic pulses in DO after floods—was most important during the Winter, whereas the Aquatic driver—characterized by variability over tidal, diel, and lunar cycles—was most important during the Summer. We explored how future climate change scenarios could alter the drivers of DO variability using a cumulative sums driver–response framework. Our results suggest that under climate change, Aquatic and Climatic drivers may increase in importance during the Summer, potentially linked to changing metabolic regimes and sea level, with Terrestrial driver importance potentially increasing during the Winter. Our approach highlights useful methods for understanding the spatiotemporal complexity of oxygen across coastal interfaces and quantifying the relative importance of distinct environmental drivers.

Reconnaissance Survey for Potential Energy Storage and Carbon Dioxide Storage Resources of Petroleum Reservoirs in Western Europe - Emil D. Attanasi; Philip A. Freeman (Natural Resources Research, 2023)
Energy producers and utilities use oil and gas reservoirs for gas storage to meet peak seasonal demand or to supplement intermittent energy production. These reservoirs are also suitable for the long-term storage of carbon dioxide (CO 2 ), a greenhouse gas. This study reports on a reconnaissance analysis of the potential magnitude of storage resources in 9424 known oil and gas reservoirs from 24 countries within highly industrialized western Europe. To standardize the storage resources of the oil and gas reservoirs, their volumetric capacity is expressed in terms of metric tons (mass) of CO 2 . Estimates of recoverable oil and gas at the surface are converted to subsurface volumes and then converted to the equivalent mass of CO 2 at reservoir conditions. The results indicate 36.7 gigatons of CO 2 could be stored, with oil reservoirs accounting for 32% of that total and natural gas reservoirs comprising the remaining 68%. About four-fifths of the reservoir storage resource is offshore, with about three-fourths of that offshore resource at water depths of 200 m or less. Most countries do not have the reservoir storage resources to store 15 years of CO 2 at 2017 emission levels. With few exceptions the bulk of the storage is offshore for countries that do have at least 15 years of storage. The expansion of natural gas storage for strategic purposes in abandoned onshore gas reservoirs is not expected to seriously impact CO 2 storage. The contribution of this analysis is the description of the spatial distribution of potential storage and physical accessibility.

Amide- and bis-amide-linked highly potent and broadly active antifungal agents for the treatment of invasive fungal infections- towards the discovery of pre-clinical development candidate FC12406 - Simon D. P. Baugh; Anna Chaly; Damian G. Weaver; David B. Whitman; Jeffrey C. Pelletier; Haiyan Bian; Katie B. Freeman; Allen B. Reitz; Richard W. Scott (Medicinal Chemistry Research, 2023)

Using liquid smoke to control infestations of the ham mite, Tyrophagus putrescentiae, on dry-cured hams during aging - Wenjie Shao; Yan L. Campbell; Thomas W. Phillips; Charles Freeman; Xue Zhang; Jasmine D. Hendrix; K. Virell To; Thu Dinh; William D. Rogers; M. Wes Schilling (Meat Science, 2023)

Prevalence of neonicotinoid insecticides in paired private-well tap water and human urine samples in a region of intense agriculture overlying vulnerable aquifers in eastern Iowa - Darrin A. Thompson; Dana W. Kolpin; Michelle L. Hladik; Hans-Joachim Lehmler; Shannon M. Meppelink; Matthew C. Poch; John D. Vargo; Victor A. Soupene; Nafis Md Irfan; Morgan Robinson; Kurunthachalam Kannan; Laura E. Beane Freeman; et al. (Chemosphere, 2023)

DISCOVR strain pipeline screening – Part I: Maximum specific growth rate as a function of temperature and salinity for 38 candidate microalgae for biofuels production - Michael Huesemann; Scott Edmundson; Song Gao; Sangeeta Negi; Taraka Dale; Andrew Gutknecht; Hajnalka E. Daligault; Carol K. Carr; Jacob Freeman; Theresa Kern; Shawn R. Starkenburg; Cheryl D. Gleasner; et al. (Algal Research, 2023)

Effect of four-week cannabidiol treatment on cognitive function: secondary outcomes from a randomised clinical trial for the treatment of cannabis use disorder - Rachel Lees; Lindsey A. Hines; Chandni Hindocha; Gianluca Baio; Natacha D. C. Shaban; George Stothart; Ali Mofeez; Celia J. A. Morgan; H. Valerie Curran; Tom P. Freeman (Psychopharmacology, 2023)
Rationale Chronic cannabis use is associated with impaired cognitive function. Evidence indicates cannabidiol (CBD) might be beneficial for treating cannabis use disorder. CBD may also have pro-cognitive effects; however, its effect on cognition in people with cannabis use disorder is currently unclear. Objectives We aimed to assess whether a 4-week CBD treatment impacted cognitive function. We hypothesised that CBD treatment would improve cognition from baseline to week 4, compared to placebo. Methods Cognition was assessed as a secondary outcome in a phase 2a randomised, double-blind, parallel-group and placebo-controlled clinical trial of 4-week daily 200 mg, 400 mg and 800 mg CBD for the treatment of cannabis use disorder. Participants had moderate or severe DSM-5 cannabis use disorder and intended to quit cannabis use. Our pre-registered primary cognitive outcome was delayed prose recall. Secondary cognitive outcomes were immediate prose recall, stop signal reaction time, trail-making task performance, verbal fluency and digit span. Results Seventy participants were randomly assigned to placebo ( n = 23), 400 mg CBD ( n = 24) and 800 mg CBD ( n = 23). A 200 mg group was eliminated from the trial because it was an inefficacious dose at interim analysis ( n = 12) and was not analysed here. For the primary cognitive outcome, there was no effect of CBD compared to placebo, evidenced by a lack of dose-by-time interaction at 400 mg (0.46, 95%CIs: − 1.41, 2.54) and 800 mg (0.89, 95%CIs: − 0.99, 2.81). There was no effect of CBD compared to placebo on secondary cognitive outcomes, except backwards digit span which increased following 800 mg CBD (0.30, 95%CIs: 0.02, 0.58). Conclusions In this clinical trial for cannabis use disorder, CBD did not influence delayed verbal memory. CBD did not have broad cognitive effects but 800 mg daily treatment may improve working memory manipulation. Clinical trial registration The trial was registered with ClinicalTrials.gov (NCT02044809) and the EU Clinical Trials Register (2013–000,361-36).

Seasonal variability in macroinvertebrate assemblages in paired perennial and intermittent streams in Costa Rica - Darixa D. Hernández-Abrams; Scott Connelly; Mary C. Freeman; Pablo E. Gutiérrez-Fonseca; Seth J. Wenger (Hydrobiologia, 2023)

Correction to: Clinical trial-ready patient cohorts for multiple system atrophy: coupling biospecimen and iPSC banking to longitudinal deep-phenotyping - Alain Ndayisaba; Ariana T. Pitaro; Ashlan S. Willett; Kristie A. Jones; Claudio Melo de Gusmao; Abby L. Olsen; Jisoo Kim; Eero Rissanen; Jared K. Woods; Sharan R. Srinivasan; Anna Nagy; Amanda Nagy; et al. (The Cerebellum, 2022)

Dynamic Motions of Piled Floating Pontoons Due to Boat Wake and Their Impact on Postural Stability and Safety - Elizabeth L. Freeman; Kristen D. Splinter; Ron J. Cox; Francois Flocard (Journal of Marine Science and Engineering, 2022)
Piled floating pontoons are public access structures that provide a link between land and sea. Despite floating pontoons being frequented by the public, there is limited data available to coastal or maritime engineers detailing the dynamic motions (acceleration and rotation) of these structures under wave action and the impact of these motions on public comfort and safety to inform their design. This contribution summarises results from a set of laboratory-scale physical model experiments of two varying beam width piled floating pontoons subjected to boat wake conditions. Observed accelerations and roll angles were dependent on beam-to-wavelength ratio (B/L), with the most adverse motion response observed for B/L ~0.5. Internal mass of the pontoon played a secondary role, with larger mass structures experiencing lower accelerations for similar B/L ratios. Importantly, these new experimental results reveal the complex interaction between the piles and pontoon that result in peak accelerations more than six times the nominated operational safe motion limit of 0.1g. Root mean square (RMS) accelerations were more than three times the nominated comfort limit (0.02g) and angles of rotation more than double what would be perceived as safe (6 degrees) for the boat wake conditions tested. The frequency of acceleration also suggests patrons standing on these platforms are likely to experience discomfort and instability. Laboratory results are compared against a series of field-scale experiments of pontoon motion response and patron feedback. The dynamic motion response of pontoons tested in both field-scale and laboratory experiments compared well.

Clinical Trial-Ready Patient Cohorts for Multiple System Atrophy: Coupling Biospecimen and iPSC Banking to Longitudinal Deep-Phenotyping - Alain Ndayisaba; Ariana T. Pitaro; Andrew S. Willett; Kristie A. Jones; Claudio Melo de Gusmao; Abby L. Olsen; Jisoo Kim; Eero Rissanen; Jared K. Woods; Sharan R. Srinivasan; Anna Nagy; Amanda Nagy; et al. (The Cerebellum, 2022)
Multiple system atrophy (MSA) is a fatal neurodegenerative disease of unknown etiology characterized by widespread aggregation of the protein alpha-synuclein in neurons and glia. Its orphan status, biological relationship to Parkinson’s disease (PD), and rapid progression have sparked interest in drug development. One significant obstacle to therapeutics is disease heterogeneity. Here, we share our process of developing a clinical trial-ready cohort of MSA patients (69 patients in 2 years) within an outpatient clinical setting, and recruiting 20 of these patients into a longitudinal “n-of-few” clinical trial paradigm. First, we deeply phenotype our patients with clinical scales (UMSARS, BARS, MoCA, NMSS, and UPSIT) and tests designed to establish early differential diagnosis (including volumetric MRI, FDG-PET, MIBG scan, polysomnography, genetic testing, autonomic function tests, skin biopsy) or disease activity (PBR06-TSPO). Second, we longitudinally collect biospecimens (blood, CSF, stool) and clinical, biometric, and imaging data to generate antecedent disease-progression scores. Third, in our Mass General Brigham SCiN study ( s tem c ells i n n eurodegeneration), we generate induced pluripotent stem cell (iPSC) models from our patients, matched to biospecimens, including postmortem brain. We present 38 iPSC lines derived from MSA patients and relevant disease controls (spinocerebellar ataxia and PD, including alpha-synuclein triplication cases), 22 matched to whole-genome sequenced postmortem brain. iPSC models may facilitate matching patients to appropriate therapies, particularly in heterogeneous diseases for which patient-specific biology may elude animal models. We anticipate that deeply phenotyped and genotyped patient cohorts matched to cellular models will increase the likelihood of success in clinical trials for MSA.

Differential Regulation of Mouse Hippocampal Gene Expression Sex Differences by Chromosomal Content and Gonadal Sex - Sarah R. Ocañas; Victor A. Ansere; Kyla B. Tooley; Niran Hadad; Ana J. Chucair-Elliott; David R. Stanford; Shannon Rice; Benjamin Wronowski; Kevin D. Pham; Jessica M. Hoffman; Steven N. Austad; Michael B. Stout; et al. (Molecular Neurobiology, 2022)

Integrating Pore-Scale Flow MRI and X-ray μCT for Validation of Numerical Flow Simulations in Porous Sedimentary Rocks - K. Karlsons; D. W. de Kort; F. O. Alpak; J. Dietderich; J. J. Freeman; M. Appel; M. D. Mantle; A. J. Sederman; L. F. Gladden (Transport in Porous Media, 2022)
Single-phase fluid flow velocity maps in Ketton and Estaillades carbonate rock core plugs are computed at a pore scale, using the lattice Boltzmann method (LBM) simulations performed directly on three-dimensional (3D) X-ray micro-computed tomography (µCT) images (≤ 7 µm spatial resolution) of the core plugs. The simulations are then benchmarked on a voxel-by-voxel and pore-by-pore basis to quantitative, 3D spatially resolved magnetic resonance imaging (MRI) flow velocity maps, acquired at 35 µm isotropic spatial resolution for flow of water through the same rock samples. Co-registration of the 3D experimental and simulated velocity maps and coarse-graining of the simulation to the same resolution as the experimental data allowed the data to be directly compared. First, the results are demonstrated for Ketton limestone rock, for which good qualitative and quantitative agreement was found between the simulated and experimental velocity maps. The flow-carrying microstructural features in Ketton rock are mostly larger than the spatial resolution of the µCT images, so that the segmented images are an adequate representation of the pore space. Second, the flow data are presented for Estaillades limestone, which presents a more heterogeneous case with microstructural features below the spatial resolution of the µCT images. Still, many of the complex flow patterns were qualitatively reproduced by the LBM simulation in this rock, although in some pores, noticeable differences between the LBM and MRI velocity maps were observed. It was shown that 80% of the flow (fractional summed z -velocities within pores) in the Estaillades rock sample is carried by just 10% of the number of macropores, which is an indication of the high structural heterogeneity of the rock; in the more homogeneous Ketton rock, 50% of the flow is carried by 10% of the macropores. By analysing the 3D MRI velocity map, it was found that approximately one-third of the total flow rate through the Estaillades rock is carried by microporosity—a porosity that is not captured at the spatial resolution of the µCT image.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Responsible agriculture must adapt to the wetland character of mid‐latitude peatlands - Benjamin W. J. Freeman; Chris D. Evans; Samuel Musarika; Ross Morrison; Thomas R. Newman; Susan E. Page; Giles F. S. Wiggs; Nicholle G. A. Bell; David Styles; Yuan Wen; David R. Chadwick; Davey L. Jones (Global Change Biology, 2022)
Drained, lowland agricultural peatlands are greenhouse gas (GHG) emission hotspots and a large but vulnerable store of irrecoverable carbon. They exhibit soil loss rates of ~2.0 cm yr −1 and are estimated to account for 32% of global cropland emissions while producing only 1.1% of crop kilocalories. Carbon dioxide emissions account for >80% of their terrestrial GHG emissions and are largely controlled by water table depth. Reducing drainage depths is, therefore, essential for responsible peatland management. Peatland restoration can substantially reduce emissions. However, this may conflict with societal needs to maintain productive use, to protect food security and livelihoods. Wetland agriculture strategies will, therefore, be required to adapt agriculture to the wetland character of peatlands, and balance GHG mitigation against productivity, where halting emissions is not immediately possible. Paludiculture may substantially reduce GHG emissions but will not always be viable in the current economic landscape. Reduced drainage intensity systems may deliver partial reductions in the rate of emissions, with smaller modifications to existing systems. These compromise systems may face fewer hurdles to adoption and minimize environmental harm until societal conditions favour strategies that can halt emissions. Wetland agriculture will face agronomic, socio‐economic and water management challenges, and careful implementation will be required. Diversity of values and priorities among stakeholders creates the potential for conflict. Successful implementation will require participatory research approaches and co‐creation of workable solutions. Policymakers, private sector funders and researchers have key roles to play but adoption risks would fall predominantly on land managers. Development of a robust wetland agriculture paradigm is essential to deliver resilient production systems and wider environmental benefits. The challenge of responsible use presents an opportunity to rethink peatland management and create thriving, innovative and green wetland landscapes for everyone's future benefit, while making a vital contribution to global climate change mitigation.

The acute effects of cannabidiol on emotional processing and anxiety: a neurocognitive imaging study - Michael A. P. Bloomfield; Yumeya Yamamori; Chandni Hindocha; Augustus P. M. Jones; Jocelyn L. L. Yim; Hannah R. Walker; Ben Statton; Matthew B. Wall; Rachel H. Lees; Oliver D. Howes; Valerie H. Curran; Jonathan P. Roiser; et al. (Psychopharmacology, 2022)
Rationale There is growing interest in the therapeutic potential of cannabidiol (CBD) across a range of psychiatric disorders. CBD has been found to reduce anxiety during experimentally induced stress in anxious individuals and healthy controls. However, the mechanisms underlying the putative anxiolytic effects of CBD are unknown. Objectives We sought to investigate the behavioural and neural effects of a single dose of CBD vs. placebo on a range of emotion-related measures to test cognitive-mechanistic models of its effects on anxiety. Methods We conducted a randomised, double-blind, placebo-controlled, crossover, acute oral challenge of 600 mg of CBD in 24 healthy participants on emotional processing, with neuroimaging (viewing emotional faces during functional magnetic resonance imaging) and cognitive (emotional appraisal) measures as well as subjective response to experimentally induced anxiety. Results CBD did not produce effects on brain responses to emotional faces and cognitive measures of emotional processing, or modulate experimentally induced anxiety, relative to placebo. Conclusions Given the rising popularity of CBD for its putative medical benefits, these findings question whether further research is warranted to investigate the clinical potential of CBD for the treatment of anxiety disorders.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Decision Analysis and CO2–Enhanced Oil Recovery Development Strategies - E. D. Attanasi; P. A. Freeman (Natural Resources Research, 2022)

A portable recombinase polymerase amplification assay for the rapid detection of cucurbit leaf crumple virus in watermelon leaves and fruits - Melanie Kalischuk; Katherine Hendricks; Robert Hochmuth; Josh Freeman; Pamela D. Roberts; Mathews Paret (Journal of Plant Pathology, 2022)

Development of a Seafloor Community Classification for the New Zealand Region Using a Gradient Forest Approach - Fabrice Stephenson; Ashley A. Rowden; Tom Brough; Grady Petersen; Richard H. Bulmer; John R. Leathwick; Andrew M. Lohrer; Joanne I. Ellis; David A. Bowden; Shane W. Geange; Greig A. Funnell; Debbie J. Freeman; et al. (Frontiers in Marine Science, 2022)
To support ongoing marine spatial planning in New Zealand, a numerical environmental classification using Gradient Forest models was developed using a broad suite of biotic and high-resolution environmental predictor variables. Gradient Forest modeling uses species distribution data to control the selection, weighting and transformation of environmental predictors to maximise their correlation with species compositional turnover. A total of 630,997 records (39,766 unique locations) of 1,716 taxa living on or near the seafloor were used to inform the transformation of 20 gridded environmental variables to represent spatial patterns of compositional turnover in four biotic groups and the overall seafloor community. Compositional turnover of the overall community was classified using a hierarchical procedure to define groups at different levels of classification detail. The 75-group level classification was assessed as representing the highest number of groups that captured the majority of the variation across the New Zealand marine environment. We refer to this classification as the New Zealand “Seafloor Community Classification” (SCC). Associated uncertainty estimates of compositional turnover for each of the biotic groups and overall community were also produced, and an added measure of uncertainty – coverage of the environmental space – was developed to further highlight geographic areas where predictions may be less certain owing to low sampling effort. Environmental differences among the deep-water New Zealand SCC groups were relatively muted, but greater environmental differences were evident among groups at intermediate depths in line with well-defined oceanographic patterns observed in New Zealand’s oceans. Environmental differences became even more pronounced at shallow depths, where variation in more localised environmental conditions such as productivity, seafloor topography, seabed disturbance and tidal currents were important differentiating factors. Environmental similarities in New Zealand SCC groups were mirrored by their biological compositions. The New Zealand SCC is a significant advance on previous numerical classifications and includes a substantially wider range of biological and environmental data than has been attempted previously. The classification is critically appraised and considerations for use in spatial management are discussed.

Machine Learning Can Assign Geologic Basin to Produced Water Samples Using Major Ion Geochemistry - Jenna L. Shelton; Aaron M. Jubb; Samuel W. Saxe; Emil D. Attanasi; Alexei V. Milkov; Mark Engle; Philip A. Freeman; Christopher A. Shaffer; Madalyn S. Blondes (Natural Resources Research, 2021)
Understanding the geochemistry of waters produced during petroleum extraction is essential to informing the best treatment and reuse options, which can potentially be optimized for a given geologic basin. Here, we used the US Geological Survey’s National Produced Waters Geochemical Database (PWGD) to determine if major ion chemistry could be used to classify accurately a produced water sample to a given geologic basin based on similarities to a given training dataset. Two datasets were derived from the PWGD: one with seven features but more samples (PWGD7), and another with nine features but fewer samples (PWGD9). The seven-feature dataset, prior to randomly generating a training and testing (i.e., validation) dataset, had 58,541 samples, 20 basins, and was classified based on total dissolved solids (TDS), bicarbonate (HCO 3 ), Ca, Na, Cl, Mg, and sulfate (SO 4 ). The nine-feature dataset, prior to randomly splitting into a training and testing (i.e., validation) dataset, contained 33,271 samples, 19 basins, and was classified based on TDS, HCO 3 , Ca, Na, Cl, Mg, SO 4 , pH, and specific gravity. Three supervised machine learning algorithms—Random Forest, k-Nearest Neighbors, and Naïve Bayes—were used to develop multi-class classification models to predict a basin of origin for produced waters using major ion chemistry. After training, the models were tested on three different datasets: Validation7, Validation9, and one based on data absent from the PWGD. Prediction accuracies across the models ranged from 23.5 to 73.5% when tested on the two PWGD-based datasets. A model using the Random Forest algorithm predicted most accurately compared to all other models tested. The models generally predicted basin of origin more accurately on the PWGD7-based dataset than on the PWGD9-based dataset. An additional dataset, which contained data not in the PWGD, was used to test the most accurate model; results suggest that some basins may lack geochemical diversity or may not be well described, while others may be geochemically diverse or are well described. A compelling result of this work is that a produced water basin of origin can be determined using major ions alone and, therefore, deep basinal fluid compositions may not be as variable within a given basin as previously thought. Applications include predicting the geochemistry of produced fluid prior to drilling at different intervals and assigning historical produced water data to a producing basin.

Oklahoma Nathan Shock Aging Center — assessing the basic biology of aging from genetics to protein and function - Holly Van Remmen; Willard M. Freeman; Benjamin F. Miller; Michael Kinter; Jonathan D. Wren; Ann Chiao; Rheal A. Towner; Timothy A. Snider; William E. Sonntag; Arlan Richardson (GeroScience, 2021)

Mineralogical and chemical comparison of carbonate from sites selected for cement production with limestone used in commercial operations - Freeman E. D. Senzani; Antoine F. Mulaba-Bafubiandi (Arabian Journal of Geosciences, 2021)

Mutualism Wildlife Value Orientations Predict Support for Messages About Distance-Related Wildlife Conflict - Stephanie Freeman; B. Derrick Taff; Zachary D. Miller; Jacob A. Benfield; Peter Newman (Environmental Management, 2021)

The species awareness index as a conservation culturomics metric for public biodiversity awareness - Joseph W. Millard; Richard D. Gregory; Kate E. Jones; Robin Freeman (Conservation Biology, 2021)
Although threats to global biodiversity are well known, slowing current rates of biodiversity loss remains a challenge. The Aichi targets set out 20 goals on which the international community should act to alleviate biodiversity decline, 1 of which (Target 1) aims to raise public awareness of the importance of biodiversity. Although conventional indicators for Target 1 are of low spatial and temporal coverage, conservation culturomics metrics show how biodiversity awareness can be quantified at the global scale. Following methods used for the Living Planet Index, we devised a species awareness index (SAI) to measure change in species awareness based on Wikipedia views. We calculated this index at the page level for 41,197 species listed by the International Union for Conservation of Nature (IUCN) across 10 Wikipedia languages and >2 billion views from 1 July 2015 to 30 March 2020. Bootstrapped indices for the page‐level SAI showed that overall awareness of biodiversity increased marginally over time, although there were differences among taxonomic classes and languages. Among taxonomic classes, overall awareness increased fastest for reptiles and slowest for amphibians. Among languages, overall species awareness increased fastest for Japanese and slowest for Chinese and German users. Although awareness of species as a whole increased and was significantly higher for traded species, from January 2016 through January 2020, change in awareness appeared not to be strongly related to whether the species is traded or is a pollinator. As a data source for public biodiversity awareness, the SAI could be integrated into the Conservation International Biodiversity Engagement Indicator.

Climate‐driven carry‐over effects negatively influence population growth rate in a food‐caching boreal passerine - Alex O. Sutton; Dan Strickland; Nikole E. Freeman; D. Ryan Norris (Global Change Biology, 2021)
Understanding how events throughout the annual cycle are linked is important for predicting variation in individual fitness, but whether and how carry‐over effects scale up to influence population dynamics is poorly understood. Using 38 years of demographic data from Algonquin Provincial Park, Ontario, and a full annual cycle integrated population model, we examined the influence of environmental conditions and density on the population growth rate of Canada jays ( Perisoreus canadensis ), a resident boreal passerine that relies on perishable cached food for over‐winter survival and late‐winter breeding. Our results demonstrate that fall environmental variables, most notably the number of freeze–thaw events, carried over to influence late‐winter fecundity, which, in turn, was the main vital rate driving population growth. These results are consistent with the hypothesis that warmer and more variable fall conditions accelerate the degradation of perishable stored food that is relied upon for successful reproduction. Future warming during the fall and winter may compromise the viability of cached food that requires consistent subzero temperatures for effective preservation, potentially exacerbating climate‐driven carry‐over effects that impact long‐term population dynamics.

Conscious and unconscious brain responses to food and cocaine cues - Corinde E. Wiers; Jizheng Zhao; Peter Manza; Kristina Murani; Veronica Ramirez; Amna Zehra; Clara Freeman; Kai Yuan; Gene-Jack Wang; Sükrü Barış Demiral; Anna Rose Childress; Dardo Tomasi; et al. (Brain Imaging and Behavior, 2021)

Environmental conditions modulate compensatory effects of site dependence in a food‐caching passerine - Alex O. Sutton; Dan Strickland; Nikole E. Freeman; D. Ryan Norris (Ecology, 2021)
Although density regulates the abundance of most wild animal populations by influencing vital rates, such as fecundity and survival, the mechanisms responsible for generating negative density dependence are unclear for many species. Site dependence occurs when there is preferential filling of high‐quality territories, which results in higher per capita vital rates at low densities because a larger proportion of occupied territories are of high quality. Using 41 yr of territory occupancy and demographic data, we investigated whether site dependence was a mechanism acting to influence fecundity and, by extension, regulate a population of Canada Jays in Algonquin Provincial Park, Ontario, Canada. As predicted by site dependence, the proportion of occupied territories that were of high quality was negatively correlated with population density and periods of vacancy were shorter for high‐quality territories than for low‐quality territories. We also found evidence that per capita fecundity was positively related to the proportion of occupied territories that were of high quality, but only when environmental conditions, which influence the entire population, were otherwise poor for breeding. Our results suggest that site dependence likely plays a role in regulating this population but that environmental conditions can modulate the strength of density dependence.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Molecular changes in transcription and metabolic pathways underlying muscle atrophy in the CuZnSOD null mouse model of sarcopenia - Kavithalakshmi Sataranatarajan; Gavin Pharaoh; Jacob L. Brown; Rojina Ranjit; Katarzyna M. Piekarz; Kaitlyn Street; Jonathan D. Wren; Constantin Georgescu; Caroline Kinter; Michael Kinter; Willard M. Freeman; Arlan Richardson; et al. (GeroScience, 2020)

Ensuring tests of conservation interventions build on existing literature - William J. Sutherland; Sergio Ticul Alvarez‐Castañeda; Tatsuya Amano; Roberto Ambrosini; Philip Atkinson; John M. Baxter; Alexander L. Bond; Philip J. Boon; Katherine L. Buchanan; Jos Barlow; Giuseppe Bogliani; Olivia M. Bragg; et al. (Conservation Biology, 2020)

Quantification of observable behaviors induced by typical and atypical kappa-opioid receptor agonists in male rhesus monkeys - S. L. Huskinson; D. M. Platt; M. Brasfield; M. E. Follett; T. E. Prisinzano; B. E. Blough; K. B. Freeman (Psychopharmacology, 2020)

Growth Drivers of Bakken Oil Well Productivity - E. D. Attanasi; P. A. Freeman (Natural Resources Research, 2020)
This paper identifies the drivers of the phenomenal growth in productivity in hydraulically fractured horizontal oil wells producing from the middle member of the Bakken Formation in North Dakota. The data show a strong underlying spatial component and somewhat weaker temporal component. Drivers of the spatial component are favorable reservoir conditions. The temporal component of well productivity growth is driven by increasing the number of fracture treatments and by increasing the volume of proppant and injection fluids used on a per fracture treatment basis. Random Forest, a nonparametric modeling procedure often applied in the context of machine learning, is used to identify the relative importance of geologic and well completion factors that have driven the growth in Bakken well productivity. The findings of this study suggest that a significant part of the well productivity increases during the period from 2010 to 2015 has been the result of improved well site selection. For the more recent period, that is, from 2015 through 2017, part of the improved well productivity has resulted from substantial increases in the proppant and injection fluids used per stage and per well.

Pesticide use and risk of Hodgkin lymphoma: results from the North American Pooled Project (NAPP) - Lidija Latifovic; Laura E. Beane Freeman; John J. Spinelli; Manisha Pahwa; Linda Kachuri; Aaron Blair; Kenneth P. Cantor; Shelia Hoar Zahm; Dennis D. Weisenburger; John R. McLaughlin; James A. Dosman; Punam Pahwa; et al. (Cancer Causes & Control, 2020)
Purpose The purpose of this study was to investigate associations between pesticide exposures and risk of Hodgkin lymphoma (HL) using data from the North American Pooled Project (NAPP). Methods Three population-based studies conducted in Kansas, Nebraska, and six Canadian provinces (HL = 507, Controls = 3886) were pooled to estimate odds ratios and 95% confidence intervals for single (never/ever) and multiple (0, 1, 2–4, ≥ 5) pesticides used, duration (years) and, for select pesticides, frequency (days/year) using adjusted logistic regression models. An age-stratified analysis (≤ 40/ > 40 years) was conducted when numbers were sufficient. Results In an analysis of 26 individual pesticides, ever use of terbufos was significantly associated with HL (OR: 2.53, 95% CI 1.04–6.17). In age-stratified analyses, associations were stronger among those ≤ 40 years of age. No significant associations were noted among those > 40 years old; however, HL cases ≤ 40 were three times more likely to report ever using dimethoate (OR: 3.76 95% CI 1.02–33.84) and almost twice as likely to have ever used malathion (OR: 1.86 95% CI 1.00–3.47). Those ≤ 40 years of age reporting use of 5 + organophosphate insecticides had triple the odds of HL (OR: 3.00 95% CI 1.28–7.03). Longer duration of use of 2,4-D, ≥ 6 vs. 0 years, was associated with elevated odds of HL (OR: 2.59 95% CI 1.34–4.97). Conclusion In the NAPP, insecticide use may increase the risk of HL, but results are based on small numbers.

Raising young with limited resources: supplementation improves body condition and advances fledging of Canada Jays - Nikole E. Freeman; D. Ryan Norris; Alex O. Sutton; Amy E. M. Newman (Ecology, 2020)
Food availability early in life can play a vital role in an individual's development and success, but experimental evidence for the direct effects of food on body condition, physiology, and survival of young animals in the wild is still relatively scarce. Food‐caching Canada Jays ( Perisoreus canadensis ) begin breeding in the late winter and, therefore, rely on either cached food or seemingly limited quantities of fresh food to feed nestlings in the early spring. Using a 2‐yr food supplementation experiment conducted during the nestling period and 40 yr of observational data on food supplemented by the public, we examined whether food quantity during early life influenced the physiology, body condition, timing of fledging, and survival of young Canada Jays in Algonquin Provincial Park, Ontario, Canada . Experimental food supplementation of breeding pairs advanced the fledging date of young by 24% (5.5 d) compared to controls. In 1 yr of the experiment, nestlings raised on experimentally supplemented territories had lower feather corticosterone concentrations and were in higher body condition than controls. Across treatment and control nests, young that successfully fledged had lower concentrations of feather corticosterone and were in higher body condition than those that did not fledge. Based on 40 yr of observational data, nestling body condition was positively related to the degree of food supplementation by park visitors and nestlings in higher body condition were more likely to be observed in the population in the following fall. Our results demonstrate how food availability early in life can have important downstream consequences on metrics related to individual fitness, including first year survival.

Impacts of Urbanization and Development on Estuarine Ecosystems and Water Quality - Lauren A. Freeman; D. Reide Corbett; Allison M. Fitzgerald; Daniel A. Lemley; Antonietta Quigg; Cecily N. Steppe (Estuaries and Coasts, 2019)

A boreal songbird's 20,000 km migration across North America and the Atlantic Ocean - William V. DeLuca; Bradley K. Woodworth; Stuart A. Mackenzie; Amy E. M. Newman; Hilary A. Cooke; Laura M. Phillips; Nikole E. Freeman; Alex O. Sutton; Lila Tauzer; Carol McIntyre; Iain J. Stenhouse; Scott Weidensaul; et al. (Ecology, 2019)

The buzz segment of Savannah sparrow song is a population marker - Heather Williams; Clint W. Robins; D. Ryan Norris; Amy E. M. Newman; Corey R. Freeman-Gallant; Nathaniel T. Wheelwright; Daniel J. Mennill (Journal of Ornithology, 2019)

Role of DNA methylation in the dietary restriction mediated cellular memory - Archana Unnikrishnan; Jordan Jackson; Stephanie A. Matyi; Niran Hadad; Benjamin Wronowski; Constantin Georgescu; Karla P. Garrett; Jonathan D. Wren; Willard M. Freeman; Arlan Richardson (GeroScience, 2017)

ICOADS Release 3.0: a major update to the historical marine climate record - Eric Freeman; Scott D. Woodruff; Steven J. Worley; Sandra J. Lubker; Elizabeth C. Kent; William E. Angel; David I. Berry; Philip Brohan; Ryan Eastman; Lydia Gates; Wolfgang Gloeden; Zaihua Ji; et al. (International Journal of Climatology, 2017)
We highlight improvements to the International Comprehensive Ocean‐Atmosphere Data Set ( ICOADS ) in the latest Release 3.0 ( R3 .0; covering 1662–2014). ICOADS is the most widely used freely available collection of surface marine observations, providing data for the construction of gridded analyses of sea surface temperature, estimates of air–sea interaction and other meteorological variables. ICOADS observations are assimilated into all major atmospheric, oceanic and coupled reanalyses, further widening its impact. R3 .0 therefore includes changes designed to enable effective exchange of information describing data quality between ICOADS , reanalysis centres, data set developers, scientists and the public. These user‐driven innovations include the assignment of a unique identifier ( UID ) to each marine report – to enable tracing of observations, linking with reports and improved data sharing. Other revisions and extensions of the ICOADS ' International Maritime Meteorological Archive common data format incorporate new near‐surface oceanographic data elements and cloud parameters. Many new input data sources have been assembled, and updates and improvements to existing data sources, or removal of erroneous data, made. Coupled with enhanced ‘preliminary’ monthly data and product extensions past 2014, R3 .0 provides improved support of climate assessment and monitoring, reanalyses and near‐real‐time applications.

Illegal Trade of Marine Mammal Bone Exposed: Simple Test Identifies Bones of “Mermaid Ivory” or Steller's Sea Cow (Hydrodamalis gigas) - Lorelei D. Crerar; Elizabeth W. Freeman; Daryl P. Domning; E. Christien Michael Parsons (Frontiers in Marine Science, 2017)

The neuronal metabolite NAA regulates histone H3 methylation in oligodendrocytes and myelin lipid composition - N. K. Singhal; H. Huang; S. Li; R. Clements; J. Gadd; A. Daniels; E. E. Kooijman; P. Bannerman; T. Burns; F. Guo; D. Pleasure; E. Freeman; et al. (Experimental Brain Research, 2017)

Transformations in DOC along a source to sea continuum; impacts of photo-degradation, biological processes and mixing - Timothy G. Jones; Chris D. Evans; Davey L. Jones; Paul W. Hill; Chris Freeman (Aquatic Sciences, 2016)

The greenhouse gas (GHG) emissions associated with aquatic carbon removal during drinking water treatment - Timothy G. Jones; Chris D. Evans; Chris Freeman (Aquatic Sciences, 2016)

Evidence for different QTL underlying the immune and hypersensitive responses of Eucalyptus globulus to the rust pathogen Puccinia psidii - J. B. Butler; J. S. Freeman; R. E. Vaillancourt; B. M. Potts; M. Glen; D. J. Lee; G. S. Pegg (Tree Genetics & Genomes, 2016)

Field-Scale Simulation of Production from Oceanic Gas Hydrate Deposits - Matthew T. Reagan; George J. Moridis; Jeffery N. Johnson; Lehua Pan; Craig M. Freeman; Lehua Pan; Katie L. Boyle; Noel D. Keen; Jarle Husebo (Transport in Porous Media, 2015)

Comparison of trends in butterfly populations between monitoring schemes - D. B. Roy; E. F. Ploquin; Z. Randle; K. Risely; M. S. Botham; I. Middlebrook; D. Noble; K. Cruickshanks; S. N. Freeman; T. M. Brereton (Journal of Insect Conservation, 2015)

Evaluation of Development Options for Alaska North Slope Viscous and Heavy Oil - Emil D. Attanasi; Philip A. Freeman (Natural Resources Research, 2015)

Infilled Ditches are Hotspots of Landscape Methane Flux Following Peatland Re-wetting - Mark. D. A. Cooper; Christopher. D. Evans; Piotr Zielinski; Peter. E. Levy; Alan Gray; Mike Peacock; David Norris; Nathalie Fenner; Christopher Freeman (Ecosystems, 2014)

Lay Navigator Model for Impacting Cancer Health Disparities - Cathy D. Meade; Kristen J. Wells; Mariana Arevalo; Ercilia R. Calcano; Marlene Rivera; Yolanda Sarmiento; Harold P. Freeman; Richard G. Roetzheim (Journal of Cancer Education, 2014)

Commercial Possibilities for Stranded Conventional Gas from Alaska’s North Slope - Emil D. Attanasi; Philip A. Freeman (Natural Resources Research, 2014)

Joint effects between five identified risk variants, allergy, and autoimmune conditions on glioma risk - Mahboobeh Safaeian; Preetha Rajaraman; Patricia Hartge; Meredith Yeager; Martha Linet; Mary Ann Butler; Avima M. Ruder; Mark P. Purdue; Ann Hsing; Laura Beane-Freeman; Jane A. Hoppin; Demetrius Albanes; et al. (Cancer Causes & Control, 2013)

Rock lobster biology and ecology: contributions to understanding through the Leigh Marine Laboratory 1962–2012 - AB MacDiarmid; D Freeman; S Kelly (New Zealand Journal of Marine and Freshwater Research, 2013)
We review the contributions from research conducted through the Leigh Marine Laboratory (LML) since its establishment in 1962, to the understanding of the biology and ecology of the rock lobster, Jasus edwardsii. The number of publications (103 since 1978), their breadth of subject matter, and their frequency of citation indicate the influence of this research effort. The development of an underwater population sampling tool at the LML has been key to the research on lobster distribution, abundance, size structure and sex ratios. These, in turn, allowed significant insights into the impact of fishing on lobster populations, population recovery in marine reserves, the mating system of lobsters, and the cascading effects of lobster removal on reef communities. Other key research has focused on the planktonic larval and post‐larval stages. It is likely that J. edwardsii has received a greater level of ecological research effort through the LML than any other species. The location of the LML on a stretch of rocky coastline with year‐round easy access to the field, and the availability of a rebuilding population of J. edwardsii in an adjacent marine reserve, allowed coupled laboratory and field research to rapidly develop without the confounding effects of fishing. The LML is well placed to address outstanding questions about lobster biology and ecology, and to further contribute to the conservation and management of this important resource.

Associative blocking to reward-predicting cues is attenuated in ketamine users but can be modulated by images associated with drug use - Tom P. Freeman; Celia J. A. Morgan; Fiona Pepper; Oliver D. Howes; James M. Stone; H. Valerie Curran (Psychopharmacology, 2013)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Acidity controls on dissolved organic carbon mobility in organic soils - Chris D. Evans; Tim G. Jones; Annette Burden; Nick Ostle; Piotr Zieliński; Mark D. A. Cooper; Mike Peacock; Joanna M. Clark; Filip Oulehle; David Cooper; Chris Freeman (Global Change Biology, 2012)
Dissolved organic carbon ( DOC ) concentrations in surface waters have increased across much of E urope and N orth A merica, with implications for the terrestrial carbon balance, aquatic ecosystem functioning, water treatment costs and human health. Over the past decade, many hypotheses have been put forward to explain this phenomenon, from changing climate and land management to eutrophication and acid deposition. Resolution of this debate has been hindered by a reliance on correlative analyses of time series data, and a lack of robust experimental testing of proposed mechanisms. In a 4 year, four‐site replicated field experiment involving both acidifying and deacidifying treatments, we tested the hypothesis that DOC leaching was previously suppressed by high levels of soil acidity in peat and organo‐mineral soils, and therefore that observed DOC increases a consequence of decreasing soil acidity. We observed a consistent, positive relationship between DOC and acidity change at all sites. Responses were described by similar hyperbolic relationships between standardized changes in DOC and hydrogen ion concentrations at all sites, suggesting potentially general applicability. These relationships explained a substantial proportion of observed changes in peak DOC concentrations in nearby monitoring streams, and application to a UK ‐wide upland soil p H dataset suggests that recovery from acidification alone could have led to soil solution DOC increases in the range 46–126% by habitat type since 1978. Our findings raise the possibility that changing soil acidity may have wider impacts on ecosystem carbon balances. Decreasing sulphur deposition may be accelerating terrestrial carbon loss, and returning surface waters to a natural, high‐ DOC condition.

Erratum to: Role of Stranded Gas from Central Asia and Russia in Meeting Europe’s Future Import Demand for Gas - Emil D. Attanasi; Philip A. Freeman (Natural Resources Research, 2012)

Neuroglial Expression of the MHCI Pathway and PirB Receptor Is Upregulated in the Hippocampus with Advanced Aging - Heather D. VanGuilder Starkey; Colleen A. Van Kirk; Georgina V. Bixler; Caesar G. Imperio; Vijay P. Kale; Jacob M. Serfass; Julie A. Farley; Han Yan; Junie P. Warrington; Song Han; Matthew Mitschelen; William E. Sonntag; et al. (Journal of Molecular Neuroscience, 2012)

Comparative epidemiology of CTX-M-14 and CTX-M-15 producing Escherichia coli: Association with distinct demographic groups in the community in New Zealand - J. T. Freeman; D. A. Williamson; H. Heffernan; M. Smith; J. E. Bower; S. A. Roberts (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

An ice‐core proxy for northerly air mass incursions into West Antarctica - Daniel A. Dixon; Paul A. Mayewski; Ian D. Goodwin; Gareth J. Marshall; Rhaelene Freeman; Kirk A. Maasch; Sharon B. Sneed (International Journal of Climatology, 2012)
A 200‐year proxy for northerly air mass incursions (NAMI) into central and western West Antarctica is developed from the examination of 19 shallow (21–150 m deep) Antarctic ice‐core non‐sea‐salt (nss) Ca 2+ concentration records. The NAMI proxy reveals a significant rise in recent decades. This rise is unprecedented for at least the past 200 years and is coincident with anthropogenically driven changes in other large‐scale Southern Hemisphere (SH) environmental phenomena such as greenhouse gas (GHG) induced warming, ozone depletion, and the associated intensification of the SH westerlies. The Hysplit trajectory model is used to examine air mass transport pathways into West Antarctica. Empirical orthogonal function analysis, in combination with trajectory results, suggests that atmospheric circulation is the dominant factor affecting nssCa 2+ concentrations throughout central and western West Antarctica. Ozone recovery will likely weaken the spring‐summer SH westerlies in the future. Consequently, Antarctica could lose one of its best defences against SH GHG warming. Copyright © 2011 Royal Meteorological Society

Y chromosome haplogroups and prostate cancer in populations of European and Ashkenazi Jewish ancestry - Zhaoming Wang; Hemang Parikh; Jinping Jia; Timothy Myers; Meredith Yeager; Kevin B. Jacobs; Amy Hutchinson; Laurie Burdett; Arpita Ghosh; Michael J. Thun; Susan M. Gapstur; W. Ryan Diver; et al. (Human Genetics, 2012)

Role of Stranded Gas from Central Asia and Russia in Meeting Europe’s Future Import Demand for Gas - Emil D. Attanasi; Philip A. Freeman (Natural Resources Research, 2012)

High rates of susceptibility to ceftazidime among globally prevalent CTX-M-producing Escherichia coli: potential clinical implications of the revised CLSI interpretive criteria - D. A. Williamson; S. A. Roberts; M. Smith; H. Heffernan; A. Tiong; C. Pope; J. T. Freeman (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Empirical Methods for Detecting Regional Trends and Other Spatial Expressions in Antrim Shale Gas Productivity, with Implications for Improving Resource Projections Using Local Nonparametric Estimation Techniques - Timothy C. Coburn; Philip A. Freeman; Emil D. Attanasi (Natural Resources Research, 2012)

Biased Sex Ratios in Plants: Theory and Trends - Jordan P. Sinclair; J. Emlen; D. C. Freeman (The Botanical Review, 2012)

Advances in winter pulse pathology research in Australia - Moin U. Salam; Jennifer A. Davidson; Geoff J. Thomas; Rebecca Ford; Roger A. C. Jones; Kurt D. Lindbeck; William J. MacLeod; Rohan B. E. Kimber; Jean Galloway; Nitin Mantri; Joop A. G. van Leur; Brenda A. Coutts; et al. (Australasian Plant Pathology, 2011)

ICOADS Release 2.5: extensions and enhancements to the surface marine meteorological archive - Scott D. Woodruff; Steven J. Worley; Sandra J. Lubker; Zaihua Ji; J. Eric Freeman; David I. Berry; Philip Brohan; Elizabeth C. Kent; Richard W. Reynolds; Shawn R. Smith; Clive Wilkinson (International Journal of Climatology, 2011)
Release 2.5 of the International Comprehensive Ocean‐Atmosphere Data Set (ICOADS) is a major update (covering 1662–2007) of the world's most extensive surface marine meteorological data collection. Building on extensive national and international partnerships, many new and improved contributing datasets have been processed into a uniform format and combined with the previous Release 2.4. The new data range from early non‐instrumental ship observations to measurements initiated in the twentieth century from buoys and other automated platform types. Improvements to existing data include replacing preliminary Global Telecommunication System (GTS) receipts with more reliable, delayed mode reports for post‐1997 data, and in the processing and quality control (QC) of humidity observations. Over the entire period of record, spatial and temporal coverage has been enriched and data and metadata quality has been improved. Along with the observations, now updated monthly in near real time, Release 2.5 includes quality‐controlled monthly summary products for 2° latitude × 2° longitude (since 1800) and 1° × 1° boxes (since 1960), together with multiple options for access to the data and products. The measured and estimated data in Release 2.5 are subject to many technical changes, multiple archive sources, and historical events throughout the more than three‐century record. Some of these data characteristics are highlighted, including known unresolved errors and inhomogeneities, which may impact climate and other research applications. Anticipated future directions for ICOADS aim to continue adding scientific value to the observations, products, and metadata, as well as strengthen the cooperative enterprise through expanded linkages to international initiatives and organisations. Copyright © 2010 Royal Meteorological Society

Recovery of logbooks and international marine data: the RECLAIM project - Clive Wilkinson; Scott D. Woodruff; Philip Brohan; Stefan Claesson; Eric Freeman; Frits Koek; Sandra J. Lubker; Catherine Marzin; Dennis Wheeler (International Journal of Climatology, 2011)
The RECovery of Logbooks and International Marine data (RECLAIM) project is a concerted, international effort to facilitate and encourage the recovery—through imaging and digitisation—of archived marine weather observations, platform and instrumental metadata and historical documentation, from many different countries. Non‐instrumental observations of wind and weather have been recorded in ships' logbooks for hundreds of years, augmented by systematic instrumental observations of sea surface and air temperatures, barometric pressure and other meteorological (and oceanographic) elements largely since the mid‐nineteenth century. Once digitised, these data are widely useful for climate studies and other avenues of scientific research—including oceanography, fisheries, maritime history and ecology—thus improvements seeking to address gaps and weaknesses in the currently available data record can be of major importance. In addition to documenting and prioritising archived ship logbook records for imaging and digitisation in support of that goal, RECLAIM provides expert assistance in the interpretation of historical marine records in relation to navigation, observational practices and recording. Since the project inception in 2005, RECLAIM has facilitated, for example, recovery of logbooks of the Dutch and English East India Companies in the nineteenth century, and of the British Royal Navy of the twentieth century. Currently the project website includes reference lists, rescued UK and US marine documents, extensive UK archive reports and detailed inventories of ship movements. A variety of other developing international linkages are discussed, including to Chilean, Dutch, French, German, Finnish, Norwegian, Swedish and US historical records. © Royal Meteorological Society and Crown Copyright 2010.

Behavioral states may be associated with distinct spatial patterns in electrocorticogram - Heracles Panagiotides; Walter J. Freeman; Mark D. Holmes; Dimitrios Pantazis (Cognitive Neurodynamics, 2011)

Temporal and spatial changes in cell wall composition in developing grains of wheat cv. Hereward - G. A. Toole; G. Le Gall; I. J. Colquhoun; C. Nemeth; L. Saulnier; A. Lovegrove; T. Pellny; M. D. Wilkinson; J. Freeman; R. A. C. Mitchell; E. N. C. Mills; P. R. Shewry (Planta, 2010)

Body mass index, effect modifiers, and risk of pancreatic cancer: a pooled study of seven prospective cohorts - Li Jiao; Amy Berrington de Gonzalez; Patricia Hartge; Ruth M. Pfeiffer; Yikyung Park; D. Michal Freedman; Mitchell H. Gail; Michael C. R. Alavanja; Demetrius Albanes; Laura E. Beane Freeman; Wong-Ho Chow; Wen-Yi Huang; et al. (Cancer Causes & Control, 2010)

The distribution and host range of the pandemic disease chytridiomycosis in Australia, spanning surveys from 1956–2007 - Kris Murray; Richard Retallick; Keith R. McDonald; Diana Mendez; Ken Aplin; Peter Kirkpatrick; Lee Berger; David Hunter; Harry B. Hines; R. Campbell; Matthew Pauza; Michael Driessen; et al. (Ecology, 2010)
Chytridiomycosis is the worst disease to affect vertebrate biodiversity on record. In Australia, it is thought to have caused the extinction of four frog species, and it threatens the survival of at least 10 more. We report the current distribution and host range of this invasive disease in Australia, which is essential knowledge for conservation management. We envisage that the data be used in a global and national context for predictive modeling, meta‐analyses, and risk assessment. Our continent‐wide data set comprises 821 sites in Australia and includes 10 183 records from >80 contributors spanning collection dates from 1956 to 2007. Sick and dead frogs from the field and apparently healthy frogs from museum collections were tested opportunistically for the presence of Batrachochytrium dendrobatidis , the fungal pathogen causing chytridiomycosis, and apparently healthy frogs and tadpoles found during surveys were tested purposively. The diagnostic tests used were histology of skin samples and quantitative PCR of skin swabs. Chytridiomycosis was found in all Australian states and the Australian Capital Territory, but not in the Northern Territory. Currently it appears to be confined to the relatively cool and wet areas of Australia, such as along the Great Dividing Range and adjacent coastal areas in the eastern mainland states of Queensland, New South Wales, and Victoria, eastern and central Tasmania, southern South Australia, and southwestern Western Australia. Batrachochytrium dendrobatidis may have been introduced into Australia via the port of Brisbane around 1978 and spread northward and southward. It did not appear to arrive in Western Australia until 1985. The earliest records from South Australia and Tasmania are from 1995 and 2004, respectively, although archival studies from these states are lacking. We also report negative findings showing that the disease does not currently occur in some areas that appear to be environmentally suitable, including Cape York Peninsula in Queensland and most of the World Heritage Area in western Tasmania. Infection with B. dendrobatidis has been recorded from 63 frog species in Australia to date, all belonging to the Hylidae, Limnodynastidae, and Myobatrachidae, with the exception of one individual of a species from the Microhylidae and the introduced cane toad of the family Bufonidae. The complete data sets corresponding to abstracts published in the Data Papers section of the journal are published electronically in Ecological Archives at 〈 http://esapubs.org/archive 〉. (The accession number for each Data Paper is given directly beneath the title.)

Microbial activity and diversity during extreme freeze–thaw cycles in periglacial soils, 5400 m elevation, Cordillera Vilcanota, Perú - S. K. Schmidt; D. R. Nemergut; A. E. Miller; K. R. Freeman; A. J. King; A. Seimon (Extremophiles, 2009)

The effects of chronic nitrogen fertilization on alpine tundra soil microbial communities: implications for carbon and nitrogen cycling - Diana R. Nemergut; Alan R. Townsend; Sarah R. Sattin; Kristen R. Freeman; Noah Fierer; Jason C. Neff; William D. Bowman; Christopher W. Schadt; Michael N. Weintraub; Steven K. Schmidt (Environmental Microbiology, 2008)
Summary Many studies have shown that changes in nitrogen (N) availability affect primary productivity in a variety of terrestrial systems, but less is known about the effects of the changing N cycle on soil organic matter (SOM) decomposition. We used a variety of techniques to examine the effects of chronic N amendments on SOM chemistry and microbial community structure and function in an alpine tundra soil. We collected surface soil (0–5 cm) samples from five control and five long‐term N‐amended plots established and maintained at the Niwot Ridge Long‐term Ecological Research (LTER) site. Samples were bulked by treatment and all analyses were conducted on composite samples. The fungal community shifted in response to N amendments, with a decrease in the relative abundance of basidiomycetes. Bacterial community composition also shifted in the fertilized soil, with increases in the relative abundance of sequences related to the Bacteroidetes and Gemmatimonadetes , and decreases in the relative abundance of the Verrucomicrobia . We did not uncover any bacterial sequences that were closely related to known nitrifiers in either soil, but sequences related to archaeal nitrifiers were found in control soils. The ratio of fungi to bacteria did not change in the N‐amended soils, but the ratio of archaea to bacteria dropped from 20% to less than 1% in the N‐amended plots. Comparisons of aliphatic and aromatic carbon compounds, two broad categories of soil carbon compounds, revealed no between treatment differences. However, G‐lignins were found in higher relative abundance in the fertilized soils, while proteins were detected in lower relative abundance. Finally, the activities of two soil enzymes involved in N cycling changed in response to chronic N amendments. These results suggest that chronic N fertilization induces significant shifts in soil carbon dynamics that correspond to shifts in microbial community structure and function.

For whom the bells toll: Networked circadian clocks - G. Mark FREEMAN; Alexis B. WEBB; Sungwon AN; Erik D. HERZOG (Sleep and Biological Rhythms, 2008)

Handedness and Grooming in Pan troglodytes: Comparative Analysis Between Findings in Captive and Wild Individuals - William D. Hopkins; Jamie L. Russell; Margaret Remkus; Hani Freeman; Steven J. Schapiro (International Journal of Primatology, 2007)

First cosmogenic 10 Be age constraint on the timing of Younger Dryas glaciation and ice cap thickness, western Scottish Highlands - Nicholas R. Golledge; Derek Fabel; Jeremy D. Everest; Stewart Freeman; Steven Binnie (Journal of Quaternary Science, 2007)
We use cosmogenic 10 Be surface exposure age techniques at a locality close to Rannoch Moor, western Scottish Highlands, in order to establish the age and chronology of its most recent glaciation. Glacial erratics and an in situ bedrock quartz vein sampled from this site—the summit of Beinn Inverveigh—have yielded zero‐erosion exposure ages of 12.9 ± 1.5 ka to 11.6 ± 1.0 ka, implying complete ice cover of the mountain during the Younger Dryas, or Loch Lomond Stadial. These results fit closely with published 14 C dates that bracket the maximum (lateral) extent of ice cap outlet glaciers, and are the first internally consistent ages to specifically address this period of glaciation in Scotland. Furthermore, the dates imply that previous palaeoglaciological reconstructions for this area may have underestimated both the thickness of the former ice cap and, by implication, its volume. © British Geological Survey/Natural Environment Research Council copyright 2007. Reproduced with the permission of BGS/NERC. Published by John Wiley & Sons, Ltd.

Diet quality affects an attractive white plumage pattern in dark-eyed juncos (Junco hyemalis) - Joel W. McGlothlin; Deborah L. Duffy; Jessica L. Henry-Freeman; Ellen D. Ketterson (Behavioral Ecology and Sociobiology, 2007)

Prediction of Resource Volumes at Untested Locations Using Simple Local Prediction Models - Emil D. Attanasi; Timothy C. Coburn; Philip A. Freeman (Natural Resources Research, 2007)

A decade of the Super Dual Auroral Radar Network (SuperDARN): scientific achievements, new techniques and future directions - G. Chisham; M. Lester; S. E. Milan; M. P. Freeman; W. A. Bristow; A. Grocott; K. A. McWilliams; J. M. Ruohoniemi; T. K. Yeoman; P. L. Dyson; R. A. Greenwald; T. Kikuchi; et al. (Surveys in Geophysics, 2007)

Hyperhydration prior to a simulated second day of the 3-day moderate intensity equestrian competition does not cause arterial hypoxemia in Thoroughbred horses - B. S. Tennent-Brown; T. E. Goetz; M. Manohar; A. S. Hassan; D. E. Freeman; J. S. Bundy; M. R. Evans (European Journal of Applied Physiology, 2006)

Degradation of benz[a]anthracene by Mycobacterium vanbaalenii strain PYR-1 - Joanna D. Moody; James P. Freeman; Carl E. Cerniglia (Biodegradation, 2005)

Cytotoxicity of Technical Grade versus Formulations of Atrazine and Acetochlor Using Mammalian Cells - A. L. Rayburn; D. D. Moody; J. L. Freeman (Bulletin of Environmental Contamination and Toxicology, 2005)

The self-incompatibility locus (S) and quantitative trait loci for self-pollination and seed dormancy in sunflower - Sonali D. Gandhi; Adam F. Heesacker; Carrie A. Freeman; Jason Argyris; Kent Bradford; Steven J. Knapp (Theoretical and Applied Genetics, 2005)

Fractal analysis of plant spatial patterns: a monitoring tool for vegetation transition shifts - C. L. Alados; Y. Pueyo; D. Navas; B. Cabezudo; A. Gonzalez; D. C. Freeman (Biodiversity and Conservation, 2005)

Admixture and diversity in West African cattle populations - A. R. FREEMAN; C. M. MEGHEN; D. E. MacHUGH; R. T. LOFTUS; M. D. ACHUKWI; A. BADO; B. SAUVEROCHE; D. G. BRADLEY (Molecular Ecology, 2004)
We present a population genetic analysis of microsatellite variation in 16 West African cattle populations. West Africa represents a unique juxtaposition of different climatic and ecological zones in a relatively small geographical area. While more humid coastal regions are inhabited by the tsetse fly, a vector which spreads trypanosomiasis among cattle, the disease is not transmitted in the drier areas outside this zone. This is the most thorough study of genetic diversity in cattle within this area, which contains genetically important trypanotolerant Bos taurus breeds. Genetic relationships among the many breeds are examined and levels of diversity are assessed. Admixture levels were determined using a variety of methods. Ancestry informative or population‐associated alleles (PAAs) were selected using populations from India, the Near East and Europe. Multivariate analysis, the admix program and model‐based Bayesian admixture analysis approaches were also employed. These analyses reveal the direct impact of ecological factors and the profound effect of admixture on the cattle of this region. They also highlight the importance of efforts to prevent further dilution of African taurine breeds by B. indicus cattle.

Identification ofTrichoderma biocontrol isolates to clades according to ap-PCR and ITS sequence analyses - M. Maymon; D. Minz; O. Barbul; A. Zveibil; Y. Elad; S. Freeman (Phytoparasitica, 2004)

Peatland carbon efflux partitioning reveals that Sphagnum photosynthate contributes to the DOC pool - N. Fenner; N. Ostle; C. Freeman; D. Sleep; B. Reynolds (Plant and Soil, 2004)

Bioinformatic analysis of primary endothelial cell gene array data illustrated by the analysis of transcriptome changes in endothelial cells exposed to VEGF-A and PlGF - Jonathan Schoenfeld; Khashayar Lessan; Nicola Johnson; D. Charnock-jones; Amanda Evans; Ekaterini Vourvouhaki; Laurie Scott; Richard Stephens; Tom Freeman; Samir Saidi; Brian Tom; Gareth Weston; et al. (Angiogenesis, 2004)

The use of reference strand‐mediated conformational analysis for the study of cheetah ( Acinonyx jubatus ) feline leucocyte antigen class II DRB polymorphisms - G. J. C. Drake; L. J. Kennedy; H. K. Auty; R. Ryvar; W. E. R. Ollier; A. C. Kitchener; A. R. Freeman; A. D. Radford (Molecular Ecology, 2004)
There is now considerable evidence to suggest the cheetah ( Acinonyx jubatus ) has limited genetic diversity. However, the extent of this and its significance to the fitness of the cheetah population, both in the wild and captivity, is the subject of some debate. This reflects the difficulty associated with establishing a direct link between low variability at biologically significant loci and deleterious aspects of phenotype in this, and other, species. Attempts to study one such region, the feline leucocyte antigen (FLA), are hampered by a general reliance on cloning and sequencing which is expensive, labour‐intensive, subject to PCR artefact and always likely to underestimate true variability. In this study we have applied reference strand‐mediated conformational analysis (RSCA) to determine the FLA–DRB phenotypes of 25 cheetahs. This technique was rapid, repeatable and less prone to polymerase chain reaction (PCR)‐induced sequence artefacts associated with cloning. Individual cheetahs were shown to have up to three FLA–DRB genes. A total of five alleles were identified (DRB*ha14–17 and DRB*gd01) distributed among four genotypes. Fifteen cheetahs were DRB*ha14/ha15/ha16/ha17, three were DRB*ha15/ha16/ha17, six were DRB*ha14/ha16/ha17 and one was DRB*ha14/ha15/ha16/ha17/gd01. Sequence analysis of DRB*gd01 suggested it was a recombinant of DRB*ha16 and DRB*ha17. Generation of new alleles is difficult to document, and the clear demonstration of such an event is unusual. This study confirms further the limited genetic variability of the cheetah at a biologically significant region. RSCA will facilitate large‐scale studies that will be needed to correlate genetic diversity at such loci with population fitness in the cheetah and other species.

Flowering phenology and compensation for herbivory in Ipomopsis aggregata - Rachael S. Freeman; Alison K. Brody; Christopher D. Neefus (Oecologia, 2003)

Differences in native soil ecology associated with invasion of the exotic annual chenopod, Halogeton glomeratus - Jeffrey J. Duda; D. Carl Freeman; John M. Emlen; Jayne Belnap; Stanley G. Kitchen; John C. Zak; Edward Sobek; Mary Tracy; James Montante (Biology and Fertility of Soils, 2003)

Potential role of the EPEC translocated intimin receptor (Tir) in host apoptotic events - H. R. Malish; N. L. Freeman; D. V. Zurawski; P. Chowrashi; J. C. Ayoob; J. W. Sanger; J. M. Sanger (Apoptosis, 2003)

Evidence that channel catfish, Ictalurus punctatus (Rafinesque), mortality is not linked to ingestion of the hepatotoxin microcystin‐LR - G S Snyder; A E Goodwin; D W Freeman (Journal of Fish Diseases, 2002)
Catfish farms located in the south‐eastern USA using brackish (3–5 g NaCl L −1 ) well water experience sporadic fish kills sometimes with high mortality. An investigation of three catastrophic losses occurring in this region identified no involvement of infectious diseases or traditional water quality problems, including oxygen, ammonia or nitrite. The high mortality and time course of the problem was indicative of exposure to a toxin. Attempts by other workers to explain the cause of this unique syndrome (high chloride associated toxicosis of catfish, HCTC), suggested that the losses might be because of microcystin‐producing blooms of Microcystis aeruginosa , but our investigations failed to support this conclusion . We found that (1) the liver histology of catfish experimentally exposed to pure microcystin‐LR is very different from that of catfish sampled during outbreaks of HCTC; (2) measurements of microcystin‐LR concentrations in the three cases were far lower than the concentration required to kill catfish by experimental immersion; (3) the HCTC toxin appears to have a short half‐life, whereas microcystin‐LR does not; (4) experimental gavage of catfish with massive amounts of microcystin‐LR does not cause the acute mortality typical of HCTC; (5) outbreaks of HCTC appear to be associated with heavy blooms of Anacystis marina , a halophytic cyanobacteria, not with blooms of M. aeruginosa .

Abstracts of presentations at the 22nd Congress of the Israeli Phytopathological Society February 12–13,2001 ARO, The Volcani Center, Bet Dagan, Israel - D. Shtienberg; M. Reuveni; N. Shegalov; D. Shegalov; D. Eshel; Ruth Ben-Arie; D. Prusky; Nadia Korolev; J. Katan; Talma Katan; A. Sharon; L. Oren; et al. (Phytoparasitica, 2001)

Sexual selection and the geography of Plasmodium infection in Savannah sparrows (Passerculus sandwichensis) - Corey R. Freeman-Gallant; Kathleen D. O’Connor; Megan E. Breuer (Oecologia, 2001)

Narrow hybrid zone between two subspecies of big sagebrush (Artemisia tridentata: Asteraceae) - John H. Graham; E. Durant McArthur; D. Carl Freeman (Oecologia, 2001)

Isolation of human intestinal bacteria metabolizing the natural isoflavone glycosides daidzin and genistin - Hor-Gil Hur; Jackson O. Lay Jr.; Richard D. Beger; James P. Freeman; Fatemeh Rafii (Archives of Microbiology, 2000)

Abstracts of Presentations at the 21st congress of the Israeli phytopathological society February 14–15, 2000 ARO, the Volcani Center, Bet Dagan, Israel - S. Droby; G. Kritzman; A. Gamliel; Miriam Austerweil; Yael Skutelski; I. Peretz-Alon; E. Becker; J. Katan; R. Cohen; M. Edelstein; Carmela Horev; Y. Burger; et al. (Phytoparasitica, 2000)

Abstracts of papers presented at the 15th conference of the weed science society of Israel - H. Eizenberg; Z. Tanaami; R. Jacobsohn; A. Lalazar; M. Hayut; M. Sibony; A. Tal; B. Rubin; M. Sibony; T. Yossef; D. Plakhine; Y. Kleifeld; et al. (Phytoparasitica, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Localization of five new Ly49 genes, including three closely related to Ly49c - Karina L. McQueen; J. Douglas Freeman; Fumio Takei; D. L. Mager (Immunogenetics, 1998)

Abstracts of Presentations at the 19th Congress of the Israeli Phytopathological Society - M. Raviv; I. Nir; Y. Pinkas; E. Shabi; S. Elisha; Marcell Maimon; Y. Szmulewich; S. Freeman; E. Shabi; Y. Nitzani; Talma Katan; Y. Luzzati; et al. (Phytoparasitica, 1998)

Iso‐electric focusing and the identification of fisheries’ waste in the diet of Westland petrels ( Procellaria westlandica ) - Amanda N. D. Freeman; Peter J. Smith (New Zealand Journal of Marine and Freshwater Research, 1998)
Iso‐electric focusing was used to identify fish tissue in Westland petrel ( Procellaria westlandica ) diet samples. Forty‐five percent of the samples from Westland petrel stomachs produced clear protein banding patterns and more than half of these were identified as species common in fisheries’ waste. Proteins in the other samples were presumably too digested for this technique. Iso‐electric focusing is a comparatively quick and inexpensive technique and is particularly useful for diet studies where flesh eaten is likely to be relatively undigested at the time of sampling.

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

The 18th congress of the israeli phytopathological society - Y. Elad; D. Shtienberg; H. Vintal; Y. Cohen; Sonia Farkash; Zipora Reshit; A. Baider; Edna Levy; I. S. Ben-Ze’ev; Y. Nitzani; Frieda Kleitman; Talma Katan; et al. (Phytoparasitica, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Sexual specialization and inbreeding avoidance in the evolution of dioecy - D. Carl Freeman; Jon Lovett Doust; Ali El-Keblawy; Kathleen J. Miglia; E. Durant McArthur (The Botanical Review, 1997)

Cohesive sediment transport on an inter-tidal zone under combined wave-tidal flow - D. P. Freeman; L. E. Coates; M. C. Ockenden; W. Roberts; J. R. West (Aquatic Ecology, 1994)

Dipeptidase-C inDrosophila melanogaster: Genetic, ontogenetic, and tissue-specific variation - Kazuo Hiraizumi; Catherine L. Hourani; Mary C. Zambarano; James E. Freeman; Karen D. Mathes (Biochemical Genetics, 1992)

Dipeptidase-C inDrosophila melanogaster: Genetic, ontogenetic, and tissue-specific variation - Kazuo Hiraizumi; Catherine L. Hourani; Mary C. Zambarano; James E. Freeman; Karen D. Mathes (Biochemical Genetics, 1992)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

Suberization and periderm development in Norchief and Red Pontiac potatoes - S. A. Ali; D. C. Nelson; T. P. Freeman (American Journal of Potato Research, 1975)

Search for a human leukemia virus - J. W. Smith; A. I. Freeman; D. Pinkel (Archives of Virology, 1967)